Low-dielectric resin composition, metal-clad laminated board and preparation method and application of low-dielectric resin composition and metal-clad laminated board
Through the cross-linking network of functional acetonide and polycyclic aromatic compounds, combined with phosphorus-containing flame retardant and filler materials, the problem of insufficient dielectric performance of copper clad material in high-frequency signal transmission is solved, and a metal clad laminate with low dielectric constant, low dielectric loss, excellent mechanical properties and high heat resistance is achieved, meeting the requirements of high-frequency and high-speed printed circuit boards.
Patent Information
- Application Number
- CN202510719401.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-08-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing copper clad materials lack dielectric performance in high-frequency signal transmission, and lack heat resistance and bonding strength. Traditional flame retardants have the risk of environmental protection and compliance and the problems of high-temperature decomposition products corrode the circuit.
Functional acenaerone and polycyclic aromatic compounds containing unsaturated carbon-carbon double bonds are used to combine phosphorus-containing flame retardants and fillers to form a low dielectric resin composition through a cross-linking network, which is used to prepare metal-covered laminates to improve dielectric properties and heat resistance, and to meet environmental protection requirements through halogen-free flame retardants.
It achieves a reduction in low dielectric constant and dielectric loss, improves glass transition temperature and thermal decomposition temperature, ensures the mechanical performance and environmental stability of high-frequency and high-speed printed circuit boards, and avoids environmental compliance risks and high-temperature decomposition corrosion.
Smart Images

Figure BDA0005429101820000021 
Figure BDA0005429101820000022 
Figure BDA0005429101820000031
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of copper clad laminates, and in particular to a low-dielectric resin composition, a metal-clad laminate, and a preparation method and application thereof. Background Art
[0002] With the rapid development of 5G communications, the Internet of Things, and high-frequency electronic devices, high-frequency and high-speed printed circuit boards (PCBs) are placing increasingly stringent performance requirements on substrate materials. In particular, resin systems with low dielectric constant (Dk), low dielectric loss (Df), high heat resistance, excellent mechanical strength, and environmental stability are required. While traditional copper-clad laminate substrates (such as epoxy resins and BT resins) offer certain processing advantages, their dielectric properties (Dk > 4.0, Df > 0.02) struggle to meet the low-loss requirements for high-frequency signal transmission above 10 GHz. Furthermore, thermal expansion mismatch and delamination are prone to occur at high temperatures, hindering high-density interconnection and high-reliability applications.
[0003] In the existing technology, polycyclic aromatic hydrocarbons (such as naphthalene and anthracene derivatives) are used to reduce the dielectric constant due to their low polarity characteristics. However, their insufficient molecular rigidity leads to limited heat resistance (Tg < 180 ° C) and cross-linking density, and the bonding strength with copper foil is low. In addition, although conventional flame retardants (such as brominated epoxy) can meet the UL 94V-0 standard through the halogen flame retardant mechanism, there are environmental compliance risks (RoHS restrictions) and high-temperature decomposition products Corrosion of circuits. Therefore, there is an urgent need to develop a resin system that has low dielectric constant, high heat resistance, halogen-free flame retardancy and process adaptability.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] The present invention provides a low-dielectric resin composition, a metal-clad laminate, and methods for preparing and using the same. The metal-clad laminate material used in circuit boards fabricated using the low-dielectric resin composition exhibits excellent low dielectric properties and high heat resistance, as well as excellent heat resistance and mechanical properties, making it suitable for the production of high-frequency, high-speed printed circuit boards (PCBs).
[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are adopted:
[0007] In a first aspect, the present invention provides a low dielectric resin composition, comprising the following components in parts by weight:
[0008]
[0009] Preferably, the functionalized acenaphthylene comprises any one or a combination of at least two of the acenaphthylenes shown in the following formula I:
[0010]
[0011] Wherein, R1, R2 and R3 are each independently selected from any one of maleimide group, amino group or epoxy group.
[0012] Preferably, the dielectric constant Dk of the functionalized acenaphthylene is 2.5 to 3.6;
[0013] Preferably, the dielectric loss Df of the functionalized acenaphthylene is 0.003 to 0.005.
[0014] Preferably, the glass transition temperature Tg of the functionalized acenaphthylene is 200-250°C.
[0015] Preferably, the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds includes any one or a combination of at least two of the compounds represented by the following formula II:
[0016]
[0017] Wherein, Y is selected from any one of fluorenyl, naphthyl, anthracenyl, phenanthrenyl, chrysenyl, pyrenyl or benzanthryl.
[0018] Preferably, the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds includes the compound represented by the following formula II-1 and / or the compound represented by the following formula II-2:
[0019]
[0020] Preferably, the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds consists of the compound represented by formula II-1 and the compound represented by formula II-2.
[0021] Preferably, the mass ratio of the compound represented by formula II-1 to the compound represented by formula II-2 is (6 to 8):(2 to 4).
[0022] Preferably, the crystal exothermic temperature of the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds is 100-120°C.
[0023] Preferably, the flame retardant comprises a phosphorus-containing flame retardant.
[0024] Preferably, the phosphorus-containing flame retardant includes any one or a combination of at least two of the phosphorus-containing flame retardants shown in the following formula III:
[0025]
[0026] Wherein, R is selected from C1-C6 linear or branched alkyl, or C6-C20 aryl.
[0027] Preferably, the R is selected from C1 to C6 linear or branched alkyl groups.
[0028] Preferably, the phosphorus-containing flame retardant includes 1,4-bis(diphenylphosphino)butane.
[0029] Preferably, the filling material comprises any one of spherical silica, crystalline silica, synthetic silica or fused silica, or a combination of at least two thereof, preferably spherical silica.
[0030] Preferably, the particle size of the filler material is 0.01 to 24 μm, preferably 0.1 to 10 μm.
[0031] Preferably, the purity of the filling material is above 99.0%.
[0032] Preferably, the toughening agent includes any one or a combination of at least two of polybutadiene, styrene-butadiene block copolymer, styrene-ethylene butylene-styrene copolymer, styrene-butadiene block copolymer, styrene-butadiene-styrene triblock copolymer, hydrogenated styrene-butadiene-styrene block copolymer or maleic anhydride grafted styrene-butadiene-styrene block copolymer elastomer.
[0033] Preferably, the cross-linking agent includes any one of pentaerythritol tetraacrylate, tricyclodecane dimethanol diacrylate or triallyl isocyanurate resin, or a combination of at least two thereof.
[0034] Preferably, the initiator includes any one of azobisisobutyronitrile, azobis(2-isopropyl)butyronitrile, azobisadiponitrile, dibenzoyl peroxide, dimethylbenzoyl peroxide, diisopropyl peroxide, dicumyl peroxide, cyclohexanone peroxide, methyl ethyl ketone peroxide, dicyclohexyl peroxide, benzoic acid peroxide, tert-butyl peroxide, butylbenzoic acid peroxide or tert-butylbenzoic acid peroxide, or a combination of at least two thereof.
[0035] Preferably, the low dielectric resin composition further comprises 70 to 150 parts of a solvent.
[0036] Preferably, the solvent includes any one of toluene, butanone, acetone, dimethylformamide, methyl ethyl ketone or propylene glycol methyl ether, or a combination of at least two thereof.
[0037] In a second aspect, the present invention provides a method for preparing the low dielectric resin composition according to the first aspect, the preparation method comprising:
[0038] Functionalized acenaphthylene, a polycyclic aromatic compound containing unsaturated carbon-carbon double bonds, a flame retardant, a filling material, a toughening agent, a crosslinking agent and an initiator are mixed to obtain the low dielectric resin composition.
[0039] Preferably, the mixing method includes: dissolving functionalized acenaphthylene, a polycyclic aromatic compound containing unsaturated carbon-carbon double bonds, a flame retardant, a filler, a toughening agent, a crosslinking agent and an initiator in a solvent to obtain the low dielectric resin composition.
[0040] In a third aspect, the present invention provides a metal-clad laminate comprising a prepreg and a metal foil; the prepreg comprises glass fiber cloth and a low-dielectric resin; wherein the low-dielectric resin is formed by curing the low-dielectric resin composition described in the first aspect.
[0041] In a fourth aspect, the present invention provides a method for preparing the metal-clad laminate, the method comprising:
[0042] Applying the low dielectric resin composition on the glass fiber cloth and semi-curing it to obtain the prepreg;
[0043] The prepreg and the metal foil are stacked and pressed to obtain the metal-clad laminate.
[0044] Preferably, the coating amount of the low dielectric resin composition is 140 to 180 g / m 2 .
[0045] Preferably, the coating line speed is 8 to 25 m / min.
[0046] Preferably, the semi-curing temperature is 110-230° C., and the semi-curing time is 3-6 minutes.
[0047] Preferably, the pressing pressure is 70-600 psi, the pressing temperature is 70-240° C., the pressing vacuum is 0.02-0.1 MPa, and the pressing time is 50-200 min.
[0048] In a fifth aspect, the present invention provides a use of the low dielectric resin composition as described in the first aspect, or the metal-clad laminate as described in the third aspect, in the preparation of a high-frequency and high-speed printed circuit board.
[0049] In a sixth aspect, the present invention provides a high-frequency and high-speed printed circuit board, comprising the low-dielectric resin composition as described in the first aspect, or the metal-clad laminate as described in the third aspect.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] (1) The present invention introduces the non-polar characteristics of the polycyclic aromatic hydrocarbon structure and the dense cross-linking between molecules to reduce dipole polarization, lower the dielectric constant (Dk) and dielectric loss (Df). The cross-linking network is densified and the aromatic ring structure is chemically inert, resisting acid, alkali, solvent and moisture corrosion.
[0052] (2) The present invention introduces functionalized acenaphthylene and a polycyclic aromatic compound containing unsaturated carbon-carbon double bonds into the low dielectric resin composition. The polycyclic rigid skeleton and cross-linked network of the functionalized acenaphthylene (formed by thermal polymerization or Diels-Alder reaction of unsaturated double bonds) greatly increase the glass transition temperature (Tg) and thermal decomposition temperature (Td) of the resin. DETAILED DESCRIPTION
[0053] Unless otherwise defined herein, scientific and technological terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0054] It should be noted that the following description sets forth specific details to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways than those described herein, and those skilled in the art may make similar generalizations without departing from the scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0055] Below in conjunction with embodiment and example, embodiment of the present invention is described in detail, but those skilled in the art will appreciate that the following embodiment and example are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work premise all fall within the scope of protection of the present invention. Unspecified conditions are carried out according to the conditions of normal conditions or manufacturer's recommendations. Reagents used or instruments not specified by the manufacturer are conventional products that can be purchased commercially.
[0056] In a first aspect, the present invention provides a low dielectric resin composition, comprising the following components in parts by weight:
[0057]
[0058] In the present invention, functionalized acenaphthylene and polycyclic aromatic compounds containing unsaturated carbon-carbon double bonds are introduced into the low-dielectric resin composition. The advantage of the combination of the two is that the polycyclic skeleton of acenaphthylene is combined with the cross-linking ability of vinyl polycyclic aromatic hydrocarbons, which not only retains the non-polar properties but also optimizes the thermal stability through cross-linking. This combination may achieve a balance between dielectric properties and heat resistance. Among them, the rigid conjugated structure of polycyclic aromatic hydrocarbons provides excellent thermal stability. The delocalization energy of the conjugated π bond is high, and more energy is required to break, thereby delaying thermal decomposition; the vinyl group forms a cross-linked structure during the polymerization process, which strengthens the connection between the molecular chains. This three-dimensional network not only restricts the movement of the chain segments, but also increases the glass transition temperature (Tg), so that the material maintains mechanical strength at high temperatures.
[0059] Therefore, the functionalized acenaphthylene and the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds cooperate with each other to significantly increase the glass transition temperature (Tg) and thermal decomposition temperature (Td) of the resin.
[0060] As an optional embodiment, the content of functionalized acenaphthylene in the low dielectric resin composition is 60 to 120 parts, for example, it can be 60 parts, 62 parts, 64 parts, 65 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 75 parts, 76 parts, 78 parts, 80 parts, 82 parts, 84 parts, 85 parts, 86 parts, 88 parts, 90 parts, 92 parts, 94 parts, 95 parts, 96 parts, 98 parts, 100 parts, 102 parts, 104 parts, 105 parts, 106 parts, 108 parts, 110 parts, 112 parts, 114 parts, 115 parts, 116 parts, 118 parts, 120 parts, etc.
[0061] As an optional embodiment, the content of the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds in the low dielectric resin composition is 60 to 120 parts, for example, it can be 60 parts, 62 parts, 64 parts, 65 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 75 parts, 76 parts, 78 parts, 80 parts, 82 parts, 84 parts, 85 parts, 86 parts, 88 parts, 90 parts, 92 parts, 94 parts, 95 parts, 96 parts, 98 parts, 100 parts, 102 parts, 104 parts, 105 parts, 106 parts, 108 parts, 110 parts, 112 parts, 114 parts, 115 parts, 116 parts, 118 parts, 120 parts, etc.
[0062] As an optional embodiment, the content of the flame retardant in the low dielectric resin composition is 5 to 15 parts, for example, it can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc.
[0063] As an optional embodiment, the content of filling material in the low dielectric resin composition is 80 to 150 parts, for example, it can be 80 parts, 85 parts, 90 parts, 95 parts, 100 parts, 105 parts, 110 parts, 115 parts, 120 parts, 125 parts, 130 parts, 135 parts, 140 parts, 145 parts, 150 parts, etc.
[0064] As an optional embodiment, the content of the toughening agent in the low dielectric resin composition is 5 to 12 parts, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, etc.
[0065] As an optional embodiment, the content of the crosslinking agent in the low dielectric resin composition is 10 to 30 parts, for example, it can be 10 parts, 12 parts, 14 parts, 15 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 25 parts, 26 parts, 28 parts, 30 parts, etc.
[0066] As an optional embodiment, the content of the initiator in the low dielectric resin composition is 0.2 to 3 parts, for example, it can be 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 part, 1.2 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.8 parts, 3 parts, etc.
[0067] As an optional embodiment, the functionalized acenaphthylene includes any one or a combination of at least two of the acenaphthylenes shown in the following formula I:
[0068]
[0069] As an optional embodiment, R1, R2 and R3 are each independently selected from any one of a maleimide group, an amino group or an epoxy group.
[0070] As a preferred embodiment, the functionalized acenaphthylene includes bis(vinylphenyl)ethane.
[0071] As a preferred embodiment, the functionalized acenaphthylene includes acenaphthylene shown in the following formula I-1:
[0072]
[0073] As an optional embodiment, the dielectric constant Dk of the functionalized acenaphthylene is 2.5 to 3.6, for example, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, etc.
[0074] As a preferred embodiment, the dielectric loss Df of the functionalized acenaphthylene is 0.003 to 0.005, for example, 0.003, 0.0035, 0.004, 0.0045, 0.005, etc.
[0075] As a preferred embodiment, the glass transition temperature Tg of the functionalized acenaphthylene is 200-250°C, for example, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, etc.
[0076] As an optional embodiment, the functionalized acenaphthylene shown in I-1 is prepared by the following route:
[0077]
[0078] As an optional embodiment, the preparation method of acenaphthylene shown in I-1 includes: reacting acenaphthylene with 4-cyclopentene-1,3-dione in the presence of a catalyst to obtain the functionalized acenaphthylene shown in I-1.
[0079] As an alternative embodiment, the catalyst comprises a Lewis acid.
[0080] As an optional embodiment, the Lewis acid includes any one of ZnCl2, BF3·Et2O or AlCl3, or a combination of at least two thereof, wherein the Lewis acid is used to increase the reaction rate and selectivity.
[0081] As an optional embodiment, the reaction of acenaphthylene and 4-cyclopentene-1,3-dione can be carried out in a non-polar or weakly polar solvent, a protic solvent, or without a solvent.
[0082] As an optional embodiment, the non-polar or weakly polar solvent includes any one of toluene, dichloromethane, and tetrahydrofuran, or a combination of at least two thereof.
[0083] As an optional embodiment, the protic solvent includes ethanol.
[0084] As an optional embodiment, the reaction temperature of the reaction of acenaphthylene and 4-cyclopentene-1,3-dione is 40-100°C, for example, it can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc.
[0085] As an optional embodiment, the reaction time of the reaction of acenaphthylene and 4-cyclopentene-1,3-dione is 6 to 10 hours, for example, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, etc.
[0086] As an optional embodiment, the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds includes any one or a combination of at least two of the compounds shown in the following formula II:
[0087]
[0088] Wherein, Y is selected from any one of fluorenyl, naphthyl, anthracenyl, phenanthrenyl, chrysenyl, pyrenyl or benzanthryl.
[0089] As a preferred embodiment, the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds includes the compound represented by the following formula II-1 and / or the compound represented by the following formula II-2:
[0090]
[0091] Wherein, the structural formula of the 9,9-bis(4-vinylbenzyl)-9H-fluorene is Formula II-1:
[0092]
[0093] Wherein, the structural formula of the 9,9-bis(2-vinylbenzyl)-9H-fluorene is Formula II-2:
[0094]
[0095] As a preferred embodiment, the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds is composed of the compound represented by formula II-1 and the compound represented by formula II-2.
[0096] As a preferred embodiment, the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds consists of 9,9-bis(4-vinylbenzyl)-9H-fluorene and 9,9-bis(2-vinylbenzyl)-9H-fluorene.
[0097] As a preferred embodiment, the mass ratio of the compound represented by formula II-1 to the compound represented by formula II-2 is (6 to 8): (2 to 4), for example, it can be 6:4, 6.5:3.5, 7:3, 7.5:2.5, 8:2, etc.
[0098] As a preferred embodiment, based on the total mass of the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds as 100%, the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds includes: 60-80% of 9,9-bis(4-vinylbenzyl)-9H-fluorene and 20-40% of 9,9-bis(2-vinylbenzyl)-9H-fluorene.
[0099] As a preferred embodiment, the content of 9,9-bis(4-vinylbenzyl)-9H-fluorene in the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds is 60-80%, for example, it can be 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, etc.
[0100] As a preferred embodiment, the content of 9,9-bis(2-vinylbenzyl)-9H-fluorene in the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds is 20-40%, for example, it can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, etc.
[0101] As a preferred embodiment, the crystal exothermic temperature of the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds is 100-120°C, for example, it can be 100°C, 102°C, 104°C, 105°C, 106°C, 108°C, 110°C, 112°C, 114°C, 115°C, 116°C, 118°C, 120°C, etc.
[0102] As an optional embodiment, the flame retardant includes a phosphorus-containing flame retardant.
[0103] As a preferred embodiment, the phosphorus-containing flame retardant includes any one or a combination of at least two of the phosphorus-containing flame retardants shown in the following formula III:
[0104]
[0105] Wherein, R is selected from C1-C6 linear or branched alkyl, or C6-C20 aryl.
[0106] As an optional embodiment, in formula III, R is selected from a C1-C6 straight or branched alkyl group, for example, it can be methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, sec-pentyl, n-hexyl, isohexyl, neohexyl, tert-hexyl, 2-methylpentyl, or 3-methylpentyl.
[0107] As an optional embodiment, in formula III, R is selected from C6-C20 aryl groups, for example, phenyl, naphthyl, anthracenyl, phenanthrenyl, pyrenyl, naphthacene, benzopyrenyl, etc.
[0108] As an optional embodiment, the filling material includes any one of spherical silica, crystalline silica, synthetic silica or fused silica, or a combination of at least two thereof.
[0109] As a preferred embodiment, the filling material is spherical silica, the main function of which is to increase the bonding force.
[0110] As an optional embodiment, the particle size of the filling material is 0.01 to 24 μm, for example, it can be 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, etc.
[0111] As a preferred embodiment, the particle size of the filler is 0.1 to 10 μm.
[0112] As a preferred embodiment, the purity of the filling material is above 99.0%, for example, it can be 99.0%, 99.1%, 99.2%, 99.3%, 99.4%, 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, etc.
[0113] As an optional embodiment, the toughening agent includes any one or a combination of at least two of polybutadiene, styrene-butadiene block copolymer, styrene-ethylene butylene-styrene copolymer, styrene-butadiene block copolymer, styrene-butadiene-styrene triblock copolymer, hydrogenated styrene-butadiene-styrene block copolymer or maleic anhydride grafted styrene-butadiene-styrene block copolymer elastomer.
[0114] As an optional embodiment, the cross-linking agent includes any one of pentaerythritol tetraacrylate, tricyclodecane dimethanol diacrylate or triallyl isocyanurate resin, or a combination of at least two thereof.
[0115] As an optional embodiment, the initiator includes any one of azobisisobutyronitrile, azobis(2-isopropyl)butyronitrile, azobisadiponitrile, dibenzoyl peroxide, dimethylbenzoyl peroxide, diisopropyl peroxide, dicumyl peroxide, cyclohexanone peroxide, methyl ethyl ketone peroxide, dicyclohexyl peroxide, benzoic acid peroxide, tert-butyl peroxide, butylbenzoic acid peroxide or tert-butylbenzoic acid peroxide, or a combination of at least two thereof.
[0116] As an optional embodiment, the low dielectric resin composition further includes 70 to 150 parts of a solvent, for example, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, 95 parts, 100 parts, 105 parts, 110 parts, 115 parts, 120 parts, 125 parts, 130 parts, 135 parts, 140 parts, 145 parts, 150 parts, etc.
[0117] As an optional embodiment, the solvent includes any one of toluene, butanone, acetone, dimethylformamide, methyl ethyl ketone or propylene glycol methyl ether, or a combination of at least two thereof.
[0118] In a second aspect, the present invention provides a method for preparing the low dielectric resin composition according to the first aspect, the preparation method comprising:
[0119] Functionalized acenaphthylene, a polycyclic aromatic compound containing unsaturated carbon-carbon double bonds, a flame retardant, a filling material, a toughening agent, a crosslinking agent and an initiator are mixed to obtain the low dielectric resin composition.
[0120] As a preferred embodiment, the mixing method includes: dissolving functionalized acenaphthylene, polycyclic aromatic compounds containing unsaturated carbon-carbon double bonds, flame retardants, fillers, toughening agents, crosslinking agents and initiators in a solvent to obtain the low dielectric resin composition.
[0121] In a third aspect, the present invention provides a metal-clad laminate comprising a prepreg and a metal foil; the prepreg comprises glass fiber cloth and a low-dielectric resin; wherein the low-dielectric resin is formed by curing the low-dielectric resin composition described in the first aspect.
[0122] As an optional embodiment, the glass fiber cloth may be E-grade, with specifications including but not limited to 1035, 1078, 1080, 2113, 2116 or 3313.
[0123] As an optional embodiment, the metal foil includes 1 / 3oz, Hoz, 1oz, 2oz, 3oz, 4oz or RTF metal foil.
[0124] As an optional embodiment, the metal clad laminate may have various sizes, including but not limited to 36×48, 37×49, 40×48, 40.5×48.5, 41×49, 42.5×48.5 or 43×49.
[0125] In a fourth aspect, the present invention provides a method for preparing the metal-clad laminate, the method comprising:
[0126] Applying the low dielectric resin composition on the glass fiber cloth and semi-curing it to obtain the prepreg;
[0127] The prepreg and the metal foil are stacked and pressed to obtain the metal-clad laminate.
[0128] As an optional embodiment, the coating amount of the low dielectric resin composition is 140 to 180 g / m 2 , for example, it can be 140g / m2 , 145g / m 2 , 150g / m 2 , 155g / m 2 , 160g / m 2 , 165g / m 2 , 170g / m 2 , 175g / m 2 , 180g / m 2 wait.
[0129] As an optional embodiment, the coating line speed is 8 to 25 m / min, for example, it can be 8 m / min, 9 m / min, 10 m / min, 11 m / min, 12 m / min, 13 m / min, 14 m / min, 15 m / min, 16 m / min, 17 m / min, 18 m / min, 19 m / min, 20 m / min, 21 m / min, 22 m / min, 23 m / min, 24 m / min, 25 m / min, etc.
[0130] As an optional embodiment, the semi-curing temperature is 110-230°C, for example, it can be 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, etc.
[0131] As an optional embodiment, the semi-curing time is 3 to 6 minutes, for example, it can be 3 minutes, 3.5 minutes, 4 minutes, 4.5 minutes, 5 minutes, 5.5 minutes, 6 minutes, etc.
[0132] As an optional embodiment, the pressing pressure is 70-600 psi, for example, it can be 70 psi, 100 psi, 150 psi, 200 psi, 250 psi, 300 psi, 350 psi, 400 psi, 450 psi, 500 psi, 550 psi, 600 psi, etc.
[0133] As an optional embodiment, the pressing temperature is 70-240°C, for example, it can be 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, etc.
[0134] As an optional embodiment, the vacuum degree of the pressing is 0.02-0.1 MPa, for example, it can be 0.02 MPa, 0.03 MPa, 0.04 MPa, 0.05 MPa, 0.06 MPa, 0.07 MPa, 0.08 MPa, 0.09 MPa, 0.1 MPa, etc.
[0135] As an optional embodiment, the pressing time is 50 to 200 min, for example, it can be 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, 130 min, 140 min, 150 min, 160 min, 170 min, 180 min, 190 min, 200 min, etc.
[0136] In a fifth aspect, the present invention provides a use of the low dielectric resin composition as described in the first aspect, or the metal-clad laminate as described in the third aspect, in the preparation of a high-frequency and high-speed printed circuit board.
[0137] In a sixth aspect, the present invention provides a high-frequency and high-speed printed circuit board, comprising the low-dielectric resin composition as described in the first aspect, or the metal-clad laminate as described in the third aspect.
[0138] The present invention is further described below by means of specific examples and comparative examples. However, it should be understood that these examples are merely provided for more detailed description and are not to be construed as limiting the present invention in any form.
[0139] Preparation Example 1
[0140] This preparation example provides a functionalized acenaphthylene, wherein the functionalized acenaphthylene is the functionalized acenaphthylene represented by the following formula I-1:
[0141]
[0142] Acenaphthylene represented by formula I-1 in this preparation example is prepared by the following steps:
[0143] Acenaphthylene (1.0 g, 6.5 mmol), 4-cyclopentene-1,3-dione (0.73 g, 6.5 mmol), and ZnCl2 (0.044 g, 0.325 mmol, 5 mol%) were dissolved in toluene (15 mL) and reacted at 110°C for 12 hours. The reaction solution was cooled to room temperature, and the toluene was evaporated under reduced pressure to obtain a crude product. The crude product was purified by silica gel column chromatography (petroleum ether / ethyl acetate volume ratio = 5:1) to collect the target component. The solvent was removed by rotary evaporation, and the product was dried under vacuum for 12 hours to obtain the functionalized acenaphthylene represented by Formula I-1 (1.2 g, 69% yield, 98% purity by HPLC).
[0144] The sources of the components in the following examples and comparative examples are as follows:
[0145]
[0146] Examples 1 to 6
[0147] Examples 1 to 7 provide seven low dielectric resin compositions and metal-clad laminates prepared therefrom; wherein the low dielectric resin compositions comprise the following components in parts by weight, as shown in Table 1 below:
[0148] Table 1
[0149]
[0150]
[0151] The metal-clad laminates provided in Examples 1 to 6 are prepared by the following steps:
[0152] (1) weighing each solid component of the low dielectric resin composition according to the above formula and dissolving it in 90 parts of toluene to obtain the low dielectric resin composition as an adhesive;
[0153] (2) The adhesive obtained in step (1) is recycled to the glue coating machine, and after pre-soaking and main soaking, the adhesive is evenly coated (the coating amount is 5.5g / m 2 ) on the glass fiber cloth, wherein the line speed of the gluing machine is controlled at 15m / min; the glass fiber cloth coated with the adhesive is baked in a drying oven at 140°C for 6 minutes to volatilize the solvent and initially react and solidify the adhesive to obtain a prepreg;
[0154] (3) Cut the semi-cured sheets into the same size, 6 sheets in a group, and then overlap with the metal foil and press. The pressing parameters are as follows (the range value indicates that it can be achieved within this range with equivalent effect): pressure of 70-600 psi; temperature of 70-240 ° C; vacuum of 0.02-0.1 MPa; pressing time of 150 min.
[0155] Examples 8-9
[0156] Examples 8 and 9 provide two low dielectric resin compositions and metal-clad laminates prepared therefrom; wherein the low dielectric resin compositions comprise the following components in parts by weight, as shown in Table 2 below:
[0157] Table 2
[0158]
[0159]
[0160] The preparation steps of the metal-clad laminates provided in Examples 1 to 6 are completely consistent with those in Examples 1 to 6 above.
[0161] Comparative Example 1
[0162] This comparative example provides a resin composition and a metal-clad laminate prepared therefrom. The only difference from Example 2 is that 1,4-bis(diphenylphosphino)butane is replaced with 15 parts by weight of decabromodiphenylethane, and the other settings are exactly the same as Example 2.
[0163] Comparative Example 2
[0164] This comparative example provides a resin composition and a metal-clad laminate prepared therefrom. The only difference from Example 2 is that the functionalized acenaphthylene shown in Formula I-1 is no longer added, the content of 9,9-bis(4-vinylbenzyl)-9H-fluorene is increased to 160 parts, and the other settings are exactly the same as Example 2.
[0165] Comparative Example 3
[0166] This comparative example provides a resin composition and a metal-clad laminate prepared therefrom. The only difference from Example 2 is that 9,9-bis(4-vinylbenzyl)-9H-fluorene is no longer added, the content of the functionalized acenaphthylene represented by Formula I-1 is increased to 160 parts, and the other settings are exactly the same as Example 2.
[0167] Comparative Example 4
[0168] This comparative example provides a resin composition and a metal-clad laminate prepared therefrom. The only difference from Example 2 is that the functionalized acenaphthylene shown in Formula I-1 is replaced with 80 parts of acenaphthylene of equal mass, and the other settings are exactly the same as Example 2.
[0169] Comparative Example 5
[0170] This comparative example provides a resin composition and a metal-clad laminate prepared therefrom. The only difference from Example 2 is that 9,9-bis(4-vinylbenzyl)-9H-fluorene is replaced with 80 parts of bisphenol fluorene of equal mass, and the other settings are exactly the same as Example 2.
[0171] Comparative Example 6
[0172] This comparative example provides a resin composition and a metal-clad laminate prepared therefrom. The only difference from Example 1 is that the content of the functionalized acenaphthylene represented by Formula I-1 is reduced to 40 parts, and the content of 9,9-bis(4-vinylbenzyl)-9H-fluorene is increased to 120 parts. The other settings are exactly the same as those in Example 1.
[0173] Comparative Example 7
[0174] This comparative example provides a resin composition and a metal-clad laminate prepared therefrom. The only difference from Example 1 is that the content of the functionalized acenaphthylene represented by Formula I-1 is increased to 120 parts, and the content of 9,9-bis(4-vinylbenzyl)-9H-fluorene is reduced to 40 parts. The other settings are exactly the same as those in Example 1.
[0175] Test Example 1
[0176] Test samples: the resin compositions provided in Examples 1 to 9 and the metal-clad laminates prepared therefrom, and the resin compositions provided in Comparative Examples 1 to 7 and the metal-clad laminates prepared therefrom.
[0177] Test method:
[0178] (I) Thermal stress tin immersion time test: Use a 50×50mm double-sided metal sample and immerse it in a 288℃ tin furnace. Record the time for the sample surface to delaminate and bubble;
[0179] (2) 288°C heat resistance test (T288): An 8 mm × 8 mm metal foil substrate was placed on a thermomechanical analyzer (TMA). The temperature was raised from room temperature to 288°C at a heating rate of 10°C / min and then maintained at 288°C. The dimensional changes of the sample were observed and the time to plate burst after 288°C was recorded.
[0180] (3) Thermal expansion coefficient: The thermal expansion coefficient of the sample shall be measured using a TMA instrument in accordance with the standards specified in IPC-TM-650 2.4.24;
[0181] (4) Dielectric constant (Dk) and dielectric dissipation factor (Df): The test methods for dielectric constant and dielectric dissipation factor shall be in accordance with the test specified in IPC-TM-650 2.5.5.9;
[0182] (V) Cracking temperature (Td): Select a square sample with a size of 6.35 mm × 6.35 mm and a minimum sample weight of 30 mg. Bake at 110±2°C for 24 hours and cool to room temperature in a desiccator. Using a thermogravimetric analyzer (TGA), increase the temperature from room temperature to 450°C at a rate of 10°C / min. Record the percentage of weight loss of the sample as the temperature rises. Report the temperature at which the weight loss is 5% as Td.
[0183] (VI) Flame retardancy: Five specimens measuring 130 mm x 12.5 mm were subjected to two combustion tests in accordance with the UL94 standard. The flame retardancy was evaluated by the total duration of combustion during the combustion test.
[0184] The specific test results are shown in Table 3 below:
[0185] Table 3
[0186]
[0187] As shown in the results in Table 3, the samples provided in Examples 1 to 6 have a Tg value of 233°C or above, a thermal stress greater than 15, a Dk (dielectric constant) of 3.8 or less, a Df (dielectric loss) of 0.0040 or less, a thermal expansion coefficient Z-CTE of 1.84 to 1.92, a UL flame retardant rating of V-0, a TD5% thermal decomposition temperature of 370°C or above, and all passed the PCT test at 2atm*3hr tin immersion for 10s*3 times. This fully demonstrates that the present invention utilizes a low-dielectric resin composition, introduces a hydrocarbon resin containing unsaturated carbon-carbon double bonds and a polycyclic aromatic compound containing unsaturated carbon-carbon double bonds, and functionalizes the polycyclic rigid skeleton and cross-linked network of acenaphthylene (formed by thermal polymerization or Diels-Alder reaction of the unsaturated double bonds), significantly increasing the glass transition temperature (Tg) and thermal decomposition temperature (Td) of the resin. Furthermore, the non-polar characteristics of the polycyclic aromatic hydrocarbon structure and the dense intermolecular cross-linking reduce dipole polarization, lowering the dielectric constant (Dk) and dielectric loss (Df). The densified cross-linked network and chemically inert aromatic ring structure provide resistance to corrosion by acids, bases, solvents, and moisture.
[0188] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low dielectric resin composition, characterized in that The low dielectric resin composition comprises the following components in parts by weight:
2. The low dielectric resin composition according to claim 1, characterized in that The functionalized acenaphthylene includes any one or a combination of at least two of the acenaphthylenes shown in the following formula I: Wherein, R1, R2 and R3 are each independently selected from any one of maleimide, amino or epoxy groups; Preferably, the functionalized acenaphthylene includes acenaphthylene represented by the following formula I-1: Preferably, the dielectric constant Dk of the functionalized acenaphthylene is 2.5 to 3.6; Preferably, the dielectric loss Df of the functionalized acenaphthylene is 0.003 to 0.005; Preferably, the glass transition temperature Tg of the functionalized acenaphthylene is 200-250°C.
3. The low dielectric resin composition according to claim 1, characterized in that The polycyclic aromatic compound containing unsaturated carbon-carbon double bonds includes any one or a combination of at least two of the compounds shown in the following formula II: Wherein, Y is selected from any one of fluorenyl, naphthyl, anthracenyl, phenanthrenyl, chrysenyl, pyrenyl or benzanthryl; Preferably, the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds includes the compound represented by the following formula II-1 and / or the compound represented by the following formula II-2: Preferably, the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds is composed of the compound represented by formula II-1 and the compound represented by formula II-2; Preferably, the mass ratio of the compound represented by formula II-1 to the compound represented by formula II-2 is (6 to 8): (2 to 4); Preferably, the crystal exothermic temperature of the polycyclic aromatic compound containing unsaturated carbon-carbon double bonds is 100-120°C.
4. The low dielectric resin composition according to claim 1, characterized in that The flame retardant includes a phosphorus-containing flame retardant, and the phosphorus-containing flame retardant includes any one or a combination of at least two of the phosphorus-containing flame retardants shown in the following formula III: Wherein, R is selected from C1-C6 linear or branched alkyl, or C6-C20 aryl; Preferably, the R is selected from C1 to C6 linear or branched alkyl groups; Preferably, the phosphorus-containing flame retardant includes 1,4-bis(diphenylphosphino)butane.
5. The low dielectric resin composition according to claim 1, characterized in that The filler material comprises any one of spherical silica, crystalline silica, synthetic silica or fused silica, or a combination of at least two thereof, preferably spherical silica; Preferably, the particle size of the filler material is 0.01 to 24 μm, preferably 0.1 to 10 μm; Preferably, the purity of the filling material is above 99.0%; Preferably, the toughening agent comprises any one or a combination of at least two of polybutadiene, styrene-butadiene block copolymer, styrene-ethylene butylene-styrene copolymer, styrene-butadiene block copolymer, styrene-butadiene-styrene triblock copolymer, hydrogenated styrene-butadiene-styrene block copolymer or maleic anhydride grafted styrene-butadiene-styrene block copolymer elastomer; Preferably, the crosslinking agent comprises any one or a combination of at least two of pentaerythritol tetraacrylate, tricyclodecane dimethanol diacrylate or triallyl isocyanurate resin; Preferably, the initiator comprises any one or a combination of at least two of azobisisobutyronitrile, azobis(2-isopropyl)butyronitrile, azobisadiponitrile, dibenzoyl peroxide, dimethylbenzoyl peroxide, diisopropyl peroxide, dicumyl peroxide, cyclohexanone peroxide, methyl ethyl ketone peroxide, dicyclohexyl peroxide, benzoic acid peroxide, tert-butyl peroxide, butylbenzoic acid peroxide or tert-butylbenzoic acid peroxide; Preferably, the low dielectric resin composition further comprises 70 to 150 parts of a solvent; Preferably, the solvent includes any one of toluene, butanone, acetone, dimethylformamide, methyl ethyl ketone or propylene glycol methyl ether, or a combination of at least two thereof.
6. A method for preparing a low dielectric resin composition according to any one of claims 1 to 5, characterized in that: The preparation method comprises: The functionalized acenaphthylene, a polycyclic aromatic compound containing unsaturated carbon-carbon double bonds, a flame retardant, a filler, a toughening agent, a crosslinking agent and an initiator are mixed to obtain the low dielectric resin composition; Preferably, the mixing method includes: dissolving functionalized acenaphthylene, a polycyclic aromatic compound containing unsaturated carbon-carbon double bonds, a flame retardant, a filler, a toughening agent, a crosslinking agent and an initiator in a solvent to obtain the low dielectric resin composition.
7. A metal-clad laminate, characterized in that: The metal-clad laminate comprises a prepreg and a metal foil; the prepreg comprises a glass fiber cloth and a low-dielectric resin; wherein the low-dielectric resin is formed by curing the low-dielectric resin composition according to any one of claims 1 to 5.
8. A method for preparing a metal-clad laminate according to claim 7, characterized in that: The preparation method comprises: Applying the low dielectric resin composition on the glass fiber cloth and semi-curing it to obtain the prepreg; Laminating and pressing the prepreg and the metal foil to obtain the metal-clad laminate; Preferably, the coating amount of the low dielectric resin composition is 140 to 180 g / m 2 ; Preferably, the coating line speed is 8 to 25 m / min; Preferably, the semi-curing temperature is 110-230°C, and the semi-curing time is 3-6 minutes; Preferably, the pressing pressure is 70-600 psi, the pressing temperature is 70-240° C., the pressing vacuum is 0.02-0.1 MPa, and the pressing time is 50-200 min.
9. Use of the low dielectric resin composition according to any one of claims 1 to 5 or the metal-clad laminate according to claim 7 in the preparation of a high-frequency and high-speed printed circuit board.
10. A high-frequency and high-speed printed circuit board, characterized in that: The high-frequency and high-speed printed wiring board comprises the low-dielectric resin composition according to any one of claims 1 to 5, or the metal-clad laminate according to claim 7.
Citation Information
Cited By
Resin composition for high frequency and high speed and application thereof
CN121086144A
